Implementation of a protocol proposed by the Brazilian National Health Surveillance Agency for antibiotic use in very low birth weight infants - Maria Cristina F. Guedes Pinto; Arnaldo C. Bueno; Alan A. Vieira (Brazilian Society of Pediatrics, 2013)
Objective: : To analyze the implementation of a protocol proposed by the Brazilian National Health Surveillance Agency (Agência Nacional de Vigilância Sanitária - ANVISA) to improve sepsis diagnosis in very low birth weight newborns. Methods: : This was a prospective study that evaluated the implementation of a protocol involving clinical and laboratory criteria (hematologic scoring system of Rodwell and C-reactive protein serial measurements), recommended by ANVISA, to improve the diagnosis of neonatal sepsis in very low birth weight newborns. The study included all patients who were born and remained in the neonatal intensive care unit until discharge or death, and excluded those with congenital diseases. The main outcomes measured in newborns before (2006-2007) and after implementation of the protocol (2008) were the rates of early and late sepsis, use of antibiotics, and mortality. Means were compared by Student's t-test and categorical variables were compared by the chi-squared test; the significance level for all tests was set at 95%. Results: : The study included 136 newborns with very low birth weight. There was no difference between groups regarding general clinical characteristics in the studied periods. There was, however, a decrease in the number of diagnoses of probable early- onset sepsis (p < 0.001), use of antimicrobial regimens (p < 0.001), and overall mortality and infection-related mortality (p = 0.009 and p = 0.049, respectively). Conclusion: : The implementation of the protocol allowed improvement of sepsis diagnosis by reducing the diagnosis of probable early-onset sepsis, thus promoting efficient antimicrobial use in this population.